From Tradition to Classroom: Leveraging Mappadendang Values in Social Studies - Namri, Siti; Sanda, Musa; Al Bayati, Adhraa Tariq Khurshid (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To find out the local wisdom values of the mappadendang tradition which can be used as a source of social studies learning at MTs DDI Amparita. To find out the implications of the local wisdom values of the Mappadendang tradition which can be used as a learning resource in social studies subjects at MTs DDI Amparita. Methodology: The research method used in this thesis is descriptive qualitative research. Data in the research process was obtained from primary data and secondary data. Data collection techniques are carried out through observation, interviews and documentation, equipped with technical data analysis using data reduction, presentation and verification. Main Findings: The results of the research show that in the local wisdom of the Mappadendang tradition, the values that can be taken as a source of learning include: 1) The value of mutual cooperation, 2) The value of family, 3) The creation of a society that upholds tolerance, 4) The value of togetherness and 5) The value of love for culture, especially the local wisdom of the mappadendang tradition . Novelty/Originality of this study: This research introduces a new perspective in social studies learning by exploring the local wisdom values of the Mappadendang tradition, which has not been integrated systematically in the formal education curriculum.